2011
DOI: 10.1364/oe.19.012021
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of superconducting niobium nitride terahertz metamaterials

Abstract: Superconducting planar terahertz (THz) metamaterials (MMs), with unit cells of different sizes, are fabricated on 200 nm-thick niobium nitride (NbN) films deposited on MgO substrates. They are characterized using THz time domain spectroscopy over a temperature range from 8.1 K to 300 K, crossing the critical temperature of NbN films. As the gap frequency (f(g) = 2Δ0/h, where Δ0 is the energy gap at 0 K and h is the Plank constant) of NbN is 1.18 THz, the experimentally observed THz spectra span a frequency ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…It has been shown that losses in metamaterials, working in and below the THz frequency range, can be greatly reduced if metallic structures are replaced by superconducting ones [1]. Additionally, superconducting meta-atoms exhibit an intrinsic tunability of their resonance frequency by magnetic field and temperature [2][3][4]. However, in both cases, the tunability arises from a suppression of the superconducting order parameter, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that losses in metamaterials, working in and below the THz frequency range, can be greatly reduced if metallic structures are replaced by superconducting ones [1]. Additionally, superconducting meta-atoms exhibit an intrinsic tunability of their resonance frequency by magnetic field and temperature [2][3][4]. However, in both cases, the tunability arises from a suppression of the superconducting order parameter, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In recent works, the THz MMs made from superconductor exhibited wideband tuning properties by thermal or magnetic-field switching. [14][15][16][17][18][19] Furthermore, the use of superconductor serves as a good method to suppress the Ohmic loss of MMs. Recently, combined with superconductor dark resonators and normal-metal radiative resonators, the hybrid MMs at microwave regime with tunable EIT-like response have been created.…”
mentioning
confidence: 99%
“…The NbN films typically have a critical temperature (T c ) of 15.8 K. The film properties and pattern formations are described in Ref. 19. Using THz time domain spectroscopy (TDS) system, the THz transmission spectra are measured over a temperature range of 8-300 K. And, a bared MgO substrate is measured as reference.…”
mentioning
confidence: 99%
“…Their operation frequency spans a huge range, from zero [51,52,53,54] to microwaves [55,18,56,19,32] and to Terahertz [11,12,37,57,38,39,40,15,58,59,41,42] and visible [45] frequencies. Moreover, researchers rely on particular superconducting devices to access the trully quantum metamaterial regime [30,60,61,62,63].…”
Section: Introductionmentioning
confidence: 99%